Analysis of anastomotic leakage after rectal surgery: A case-control study. Issue 2 (June 2015) - Tanaka, Junichiro; Nishikawa, Takeshi; Tanaka, Toshiaki; Kiyomatsu, Tomomichi; Hata, Keisuke; Kawai, Kazushige; Kazama, Shinsuke; Nozawa, Hiroaki; Yamaguchi, Hironori; Ishihara, Soichiro; Sunami, Eiji; Kitayama, Joji; et al.
Abstract Background The incidence of anastomotic leakage in rectal surgery is around 10 percent. Poor blood supply to the anastomosis, high anastomotic pressure and tension, increased operative blood loss, long operative time, and male sex are risk factors of anastomotic leakage. In the present study, we examined anastomotic leakage cases in rectal surgery at our institute and tried to ascertain the risk factors. Methods Three hundred fifty-seven consecutive patients who underwent rectal resection with anastomosis between January 2008 and October 2013 were included in the study. Patients were divided into two groups according to the existence of anastomotic leakage. Clinicopathological features, operative procedures, and intraoperative outcomes were compared between the two groups. Regarding intraoperative procedure, we focused on the ligation level of the inferior mesenteric artery, installing a transanal drainage tube in the rectum, and constructing a diverting stoma. Results Anastomotic leakage occurred in eight patients. All of them were male (p = 0.0284). There were no statistical differences in other characteristics of the patients or tumors, in operative procedures, or in intraoperative outcomes. Conclusions In the present study, no statistically significant risk factors for anastomotic leakage in rectal surgery were detected, except for male sex. However, the rate of anastomotic leakage at our institute was revealed to be rather low. Our exertion to preserve good blood flow and to prevent high tension and pressure on the anastomosis in operation may have led to this result.